2021
DOI: 10.3390/biom11101441
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline-Quinone Is More Than an Antioxidant: A Vitamin-like Accessory Factor Important in Health and Disease Prevention

Abstract: Pyrroloquinoline quinone (PQQ) is associated with biological processes such as mitochondriogenesis, reproduction, growth, and aging. In addition, PQQ attenuates clinically relevant dysfunctions (e.g., those associated with ischemia, inflammation and lipotoxicity). PQQ is novel among biofactors that are not currently accepted as vitamins or conditional vitamins. For example, the absence of PQQ in diets produces a response like a vitamin–related deficiency with recovery upon PQQ repletion in a dose-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 164 publications
0
38
0
Order By: Relevance
“…Several lines of evidence indicate that activation of AMPK–SIRT1 signaling pathway plays a major role in the suppression of lipogenesis and leads to a subsequent reduction in TG levels in HFD-fed mice [ 72 ]. PQQ promotes production of NAD+ and increases SIRT1 activity in hepatocytes [ 73 ] and animal tissues [ 74 , 75 , 76 ]. Further, a recent study demonstrated that PQQ supplementation inhibited the nuclear translocation and activity of SREBP-1c via AMPK activation, which led to a reduction in lipogenesis in HFD-fed mice [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that activation of AMPK–SIRT1 signaling pathway plays a major role in the suppression of lipogenesis and leads to a subsequent reduction in TG levels in HFD-fed mice [ 72 ]. PQQ promotes production of NAD+ and increases SIRT1 activity in hepatocytes [ 73 ] and animal tissues [ 74 , 75 , 76 ]. Further, a recent study demonstrated that PQQ supplementation inhibited the nuclear translocation and activity of SREBP-1c via AMPK activation, which led to a reduction in lipogenesis in HFD-fed mice [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 PQQ is a redox cofactor that has garnered significant attention for its potential to improve mitochondrial function and alleviate age-related conditions. Jonscher et.al., 28 make the case for the fact that PQQ shortage mimics vitamin deficiency and recovers dose-dependently with PQQ supplementation. PQQ supplementation may therefore enhance metabolic flexibility and offer immune and neuroprotection as well as Sirtuin-3 modulation and is a promising medicinal nutraceutical.…”
Section: Understanding Cirs and Mould Biotoxinsmentioning
confidence: 99%
“…PQQ is an established dietary supplement based on antioxidant and mitochondrial enhancement effects which translate to a variety of posited health-related outcomes, albeit with limited clinical evidence. , Rucker et al . have summarized the diverse biological effects of the quinone in plants, in animals, and in humans, and there is now a steady stream of clinical studies of PQQ. In a discussion of prolonging healthy aging, Ames places PQQ in a group of 10 “longevity vitamins”, described as compounds which support improving health and protect longevity, yet are not requirements for survival …”
Section: Biologymentioning
confidence: 99%